Winter report for Council Bluffs, Iowa and surrounding area, 1974 - Wigg, Melbaet al (1973)
Winter report for Council Bluffs, Iowa and surrounding area submitted by Melba Wigg. Sightings include Whistling Swan, White-fronted Geese, Red-breasted Merganser, Sandhill Crane, and Grasshopper Sparrow. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1973-1974. Epson - sheet feed/flatbed